Absence of chronic traumatic encephalopathy in retired football players with multiple concussions and neurological symptomatology - Hazrati, Lili-Naz; Tartaglia, Maria C.; Diamandis, Phedias; Davis, Karen; Green, Robin E.; Wennberg, Richard; Wong, Janice C.; Ezerins, Leo; Tator, Charles H. (Frontiers in Human Neuroscience, 2013)
Background: Chronic traumatic encephalopathy (CTE) is the term coined for the neurodegenerative disease often suspected in athletes with histories of repeated concussion and progressive dementia. Histologically, CTE is defined as a tauopathy with a distribution of tau-positive neurofibrillary tangles that is distinct from other tauopathies, and usually shows an absence of beta-amyloid deposits, in contrast to Alzheimer’s disease. Although the connection between repeated concussions and CTE-type neurodegeneration has been recently proposed, this causal relationship has not yet been firmly established. Also, the prevalence of CTE among athletes with multiple concussions is unknown. Methods: We performed a consecutive case series brain autopsy study on six retired professional football players from the Canadian Football League with histories of multiple concussions and significant neurological decline. Results: All participants had progressive neurocognitive decline prior to death; however, only 3 cases had post-mortem neuropathological findings consistent with CTE. The other 3 participants had pathological diagnoses of Alzheimer’s disease, amyotrophic lateral sclerosis and Parkinson’s disease. Moreover, the CTE cases showed co-morbid pathology of cancer, vascular disease and Alzheimer’s disease. Discussion: Our case studies highlight that not all athletes with history of repeated concussions and neurological symptomalogy present neuropathological changes of CTE. These preliminary findings support the need for further research into the link between concussion and CTE as well as the need to expand the research to other possible causes of taupathy in athletes. They point to a critical need for prospective studies with good sampling methods to allow us to understand the relationship between multiple concussions and the development of CTE.